EMISSION ANALYSIS OF LAMTORO WOOD PELLETS COMBINE PLASTIC AND SODIUM CARBONATE - Abdul Azis; Aldrin; Amri Hidayat (Forestry Study Program University Of Mataram, 2026)
Leucaena leucocephala, commonly known as lamtoro, is an invasive species that proliferates in tropical regions, including Sumbawa Island, and poses a threat to local biodiversity. Nevertheless, the abundant biomass of this plant presents an opportunity for its utilization as a renewable energy source in the form of wood pellets. This study aims to analyze the emission characteristics of lamtoro-based wood pellets substituted with plastic waste and sodium carbonate, as a strategy to enhance energy efficiency while reducing the environmental impact of solid waste. Three pellet formulations were tested: (1) 100% lamtoro as the control, (2) lamtoro mixed with 10% plastic waste, and (3) lamtoro mixed with 10% sodium carbonate. Combustion tests were conducted using a flue gas analyzer to measure the concentrations of carbon monoxide (CO), carbon dioxide (CO₂), nitrogen oxides (NOx), and particulate matter. The results indicate that the addition of plastic waste significantly increased the calorific value of the pellets but also led to higher emissions of CO and NOx. In contrast, the addition of sodium carbonate demonstrated a positive effect by reducing CO emissions by 35% and NOx by 28% compared to the control, as well as improving combustion efficiency through a catalytic mechanism in the decomposition of carbon compounds. These findings suggest that lamtoro wood pellets combined with sodium carbonate are a promising alternative bioenergy source that is environmentally friendly, supports the management of invasive species, and contributes to the diversification of renewable energy sources in rural and conservation areas.